(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study explores the complex vocabulary and expressions that learners frequently find challenging while studying the Arabic language. As the linguistic medium of the Holy Qur’an and one of the world’s richest and most intricate languages, Arabic contains numerous nuanced terms, idiomatic structures, and context-dependent meanings. The research identifies these difficult words and expressions, analyzes their linguistic features, and provides clear explanations to help students overcome comprehension obstacles. By clarifying rarely used, ambiguous, or structurally complex items, this work aims to enhance learners’ understanding and contribute to their overall language proficiency.